Perbedaan Tekanan Darah Tenaga Kerja Akibat Kebisingan Di Pt Iskandar Indah Printing Textile Surakarta - Tresto Subekti, Sigit, dr. Hardjanto, M.S., Sp.OK, Dr. Suwadji, M.Kes (2015)
Noise is unwanted sound that comes from the means of production processes or tools that work at a certain level can cause hearing loss. To prevent and control accidents and occupational diseases is necessary protection of workers. The purpose of this study was to determine the difference in blood pressure in the noise-exposed workers above and below the NAB NAB in part PT.Iskandar Beautiful Printing Textile weaving Surakarta. The method used in this study is an observational cross-sectional analytic approach. The population in this study was the work force in the weaving in PT. Iskandar Beautiful Printing Textile Surakarta as many as 140 people. By using purposive sampling selection of samples and the samples taken as many as 60 people. The statistical test used to analyze the data to test the Independent T-test. The results of this study indicate there is a difference in blood pressure in the noise-exposed workers above and below the NAB NAB with significant value in the weaving (p = 0.000 ≤ 0.05; 95%) and the value at the reacing Significant (p = 0.000 ≤ 0, 05; 95%). Based on this study the use of ear protective devices to reduce exposure to noise that can increase blood pressure.